THE UNIVERSALITY OF FEMININE VULNERABILITY: AN EAST–WEST COMPARATIVE STUDY OF ANNIE ERNAUX AND KAMALA MARKANDAYA - Bansari K. Gorakhiya; Dr. Audrey Barlow (International Educational Journal of Science and Engineering, 2026)
This study analyses the depiction of women as vulnerable and solitary in the writings of Annie Ernaux and Kamala Markandaya through an East-West literary perspective. Even though they happen in very different places and times, twentieth-century France and postcolonial India, the way they show women dealing with being banished, being alone, and having their identities shift in different social contexts is remarkably similar. The study investigates the effects of substantial social and historical factors, including modernisation, industrial advancement, and shifting gender standards, on women's self-perception, by comparing Ernaux's The Years with Markandaya's Nectar in a Sieve. This study analyses the unique narrative techniques utilised by both authors to depict women's vulnerability. It achieves this through qualitative and comparative textual analysis, drawing upon feminist literary criticism and cross-cultural literary studies. Ernaux illustrates alienation through disjointed memories and the dissolution of individual identity within shared history. Markandaya illustrates this through the harsh reality of rural poverty and social dislocation. Although the two great works of literature differ significantly in style and culture, they both illustrate the marginalisation of women in rapidly evolving societies. The study asserts that analysing these East-West literary contexts enriches our understanding of feminine vulnerability as a shared human experience shaped by various historical narratives. The book adds to the field of comparative literature by showing how works from different cultures can express the same emotional truths and by explaining the historical factors that shape them.